PROTECTION FOR CONSUMERS AGAINST BUSINESS PEOPLE WHO TRADE UNNOTIFIED BOOSTERS FROM PACKAGED SKINCARE VIA E-COMMERCE - Nur Afni Ismawati (Zhata Institut, 2024)
Business actors use internet media as a new transaction system known as e-commerce (electronic transactions). In practice, there are many problems that harm consumers as a result of using buying and selling transactions via e-commerce, one of which is the circulation of cosmetic (skincare) products without BPOM notification. The problem raised in this research is how to protect consumers against business actors who buy and sell boosters without BPOM notification from packaged skincare via e-commerce. The research method in this study uses a normative juridical approach as a legal research carried out by examining library materials or secondary data. The research results obtained show that consumer protection is carried out by forming a special team, namely cyber patrol, using an application or by means of barcodes, skincare products are distributed that have notification labels from BPOM. This form of consumer protection from e-commerce is done by providing reporting facilities, selecting sellers and providing guarantees.